The influence of electrolytes in aqueous solutions on gas-liquid mass transfer in an oscillatory flow reactor - Almeida, F. (2022)
In bioprocesses, the microorganisms growth is ruled by physical, chemical, and biological conditions being the electrolyte concentration one of the most important parameters to control. In this study, the effect of three electrolytes (HCl, NaOH, NaCl) in aqueous solutions on the volumetric (kLa) and liquid-side (kL) mass transfer coefficients and bubbles dynamics in an oscillatory flow reactor provided with smooth periodic constrictions (OFR-SPC) under different operational conditions (oscillation amplitude, x0 and frequency, f and superficial gas velocity, ug) were studied. Electrolyte concentrations below and above the transition concentration (ct) of bubbles coalescence were evaluated. The results showed insignificant inhibition of bubble coalescence, regardless of electrolyte kind and concentration. Also, no significant variations were found in kLa, kL, G, and d32 values compared with water. The three electrolytes behave similarly. Moreover, contrary to the widespread consensus in which the presence of electrolytes below the ct in aqueous systems reduces kL, in the present study in the OFR-SPC the kL results were identical to pure systems and higher than common gas-liquid contactors. According to the results, kLa was improved by increasing the oscillatory conditions and ug. The results indicate that oscillations and ug govern the hydrodynamics and mass transfer changes in aqueous electrolyte solutions. These results suggest that efficient mass transfer rates (up to 5-fold higher face to bubble columns and airlift) can be achieved with moderate power consumption, 100 W m-3, and, hence, enabling the OFR-SPC with potential for bioprocesses, replacing bubble columns and airlift bioreactors.